EPISTEMOLOGY OF ART: THE FRUITION AND ART OBJECT (Palíndromo, 2016)
In this article, we present a perspecti- ve on the subject / object, spectator / object ofart relations, reflected through the prism of the implications present in the meaning- making process of image reading. The men- tioned considerations are woven from the art object, translatedthrough the multiplicity of possible readings. These readings emphasize subjectivity as volition,however, expounding from paths of objective significance. To ex- plain this relationship, we firstexplain the ex- pressive character of the need for reason as part of the process that brings outmeaning, considering the extreme conceptual and real content of the multiple facets of the artob- ject, merged with critical ethical content. The second part of the thesis holds that art is delineated by a conceptual space, formed from the subjectivity that begins in the sub- ject that sets up the object. In this context, art objects point to the subjectivity of the artist and the spectator in the construction of meaning, through an elaborate creation process. The counterpart to this process is based on the objectivity of the real mate- rial object , which reverberates through the conceptual repertoire of the subject. We also bring to this context the autonomy present in the construction of conceptual significan- ce as substrate possible truths, in order to delineate significant areas.
Keywords: epistemology; objectivity; dubjrctivity; fruition; art object